Automotive Services in “Festung Krakau” During World War I - Gaweł, Robert (City and War, 2022)
Since antiquity, the army has been the driving force behind technological development, including the development of motorisation. While the first mechanical vehicle was constructed in 1769, the turning point in motorisation was the construction of the first diesel-powered vehicle. The Austro-Hungarian armed forces were among those interested in the possibility of using mechanical vehicles. The first tests of a military truck intended for the Austro-Hungarian army initiated a series of various mechanical vehicle tests. As a part of such tests, the first trucks appeared on the streets of Kraków in 1903. With the outbreak of the Great War, the number of military vehicles in Kraków considerably increased. The armed forces also commandeered several facilities in the city to function as workshops, fuel storehouses, and parking for their vehicles. In 1916, the first genuine military vehicle maintenance barracks and workshop complex was built in the Kraków Stronghold.